Teachers' Pre-Service Programs Curriculum to Prepare Professional Teachers at Education Faculties - Yundri Akhyar (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The competency of teachers has a significant impact on the quality of education. The Education Faculties should prepare the teacher to be a professional teacher. The research aim is to find out the the program should pre-service program at faculties to ensure the qualified teacher in the future.The research methodology relies on a review of the relevant literature. The research findingwere the curriculum of the Teachers’ Pre-Service program should be considered are pedagogy and instructional strategies, subject matter expertise, child development and educational psychology, inclusive education, classroom management, assessment and evaluation, teaching practicum, ethics and professionalism, digital literacy and educational technology by combining theoretical knowledge and practical experiences, the teachers'' pre-service program at faculties of education prepares aspiring teachers to become certified educators.